Engineered surfaces for lubricated friction: A new characterization approach for sliding surfaces. Issue 1 (2017) - Bruzzone, Alessandro A.G.; Costa, Henara L.
Abstract: While improvement of functional behaviour of engineered surfaces is fundamental, the complexity of surface phenomena in tribology makes difficult to establish consistent models to evaluate and compare functionality of textured patterns. In order to face complexity, a new approach to study textured steel surfaces produced by photochemical texturing in reciprocating sliding under hydrodynamic lubrication is presented. The approach extends hierarchically the description of surface characteristics and provides a systemic perspective that relates textures to the dissipated energy.